The Principle of Transparency Under The Artificial Intelligence Act - Vladimirova, Katia (Law Journal of New Bulgarian University, 2024)
Transparency is a basic principle of European Union law. It aims to provide information to people, thereby enabling them to participate in decision-making processes, to express their opinions and ideas, to feel secure and at ease. At the same time, transparency creates legitimacy in the European bodies and creates a prerequisite for the institutions to bear responsibility. The principle of transparency is also enshrined in the Regulation (EU) 2024/1689 of the European Parliament establishing harmonized rules on artificial intelligence or the so-called “The AI Act”. It aims to create a transparent regime for AI technologies, enabling legal entities to design and deploy AI responsibly and individuals to understand its design and use it safely.